Stymied Ambition: Does a Lack of Economic Freedom Lead to Migration? - Laura Renner; Daniel Meierrieks (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This contribution investigates the relationship between economic freedom and international migration. We argue that higher levels of economic freedom in the source countries of migration may discourage migration by generating more economic security, providing more economic opportunities and stimulating overall economic activity. Using a panel dataset on migration from 91 developing and emerging to the 20 most attractive OECD destination countries for the 1980-2010 period, we find that more economic freedom at home discourages high-skilled migration but does not matter to low-skilled migration. The negative association between economic freedom and skilled emigration also holds when we estimate dynamic-panel models that allow for endogeneity in the economic freedom-migration nexus. Our findings thus suggest that high-skilled individuals are especially responsive to the economic incentives arising from higher levels of economic freedom.
Keywords: F22; J61; J60; 330